Nacisk Stempla na Niejednorodna Półpłaszczyznę Sprężystą - Stachowicz, B.; Szefer, G. (Engineering Transactions, 1967)
An effective solution is obtained for the contact problem of a symmetric body of any form in contact without friction with a nonhomogeneous elastic semi-infinite panel (Fig, 1). The nonhomogeneity of the body is expressed by a modulus of elasticity variable with the depth, in the form (1.1). Solution is obtained by using the Airy stress function and applying the Fourier integral trans- formation.The contact problem is reduced to dual integral equations (2.19) which are reduced, by means of the Noble method to a Fredholm integral equation of the first kind (2.25), for which is obtained an approximate (for a small nonhomogeneity parameter A) but effective solution expressed in quadratures (3.20). The two examples given concern a blunt body and a wedge. The solutions (in the class of elementary functions) are obtained in both cases. The paper contains diagrams of stresses under the body in contact (Fig. 4).